2008
DOI: 10.1111/j.1365-2265.2008.03277.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of adipocyte fatty acid‐binding protein (AFABP) are increased in chronic haemodialysis (CD)

Abstract: Renal filtration appears as an important route of elimination of AFABP. Future studies should elucidate whether this adipocyte-expressed factor contributes to the increased risk of cardiovascular disease found in end-stage renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…These findings are in accordance with previous data from our group showing that serum creatinine and AFABP are independently associated in preeclampsia (27). Furthermore, we have recently demonstrated that AFABP is more than ten-fold higher in patients on chronic hemodialysis as compared with controls (30). These results further support the notion that renal elimination is a major route by which physiological AFABP serum levels are maintained.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in accordance with previous data from our group showing that serum creatinine and AFABP are independently associated in preeclampsia (27). Furthermore, we have recently demonstrated that AFABP is more than ten-fold higher in patients on chronic hemodialysis as compared with controls (30). These results further support the notion that renal elimination is a major route by which physiological AFABP serum levels are maintained.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, AFABP concentrations are significantly associated with BMI before and 6 months after gastric banding in 33 morbidly obese patients (29). In addition, we have recently shown that BMI is independently correlated with circulating AFABP in patients on chronic hemodialysis (30). Taking this published evidence into consideration, circulating AFABP appears to be regulated in a body weightdependent manner similar to the adipokine leptin.…”
Section: Discussionmentioning
confidence: 87%
“…These results are in accordance with the hypothesis that renal elimination is a route by which physiological chemerin serum levels are maintained, and they support recent findings from our group in a nonpregnant population on hemodialysis [19]. Furthermore, it is interesting to note in this context that we and others have recently suggested that renal elimination is a major mechanism influencing serum concentrations of various other adipokines including adiponectin [20], leptin [21], retinol-binding protein-4 [22], AFABP [23], and fibroblast growth factor-21 [24]. These results support the notion that markers of renal function should be included in studies concerning chemerin physiology.…”
Section: Discussionsupporting
confidence: 73%
“…These findings are in contrast to recent results indicating that other metabolic hormones, including several adipokines, show renal clearance. Thus, circulating levels of the adipokines leptin (12), adiponectin (13), retinol-binding protein-4 (14), zinc-a2-glycoprotein (15), adipocyte fatty acid-binding protein (16), fibroblast growth factor 21 (17), and chemerin (18) are significantly elevated in end-stage renal disease in contrast to the myokine irisin. It needs to be established in future experiments by which mechanisms circulating irisin is being eliminated.…”
Section: Discussionmentioning
confidence: 99%